The death of Mrs. Westaway [compact disc, unabridged] - Ware, Ruth (Simon & Schuster Audio, 2018)
After erroneously receiving a mysterious letter about a large inheritance, Hal attends the funeral of the deceased and realizes that something is very, very wrong.